Analysis of trends in sepsis mortality in Brazil and by regions from 2010 to 2019 - Nyara Rodrigues Conde de Almeida; Giovana Fonseca Pontes; Felipe Lima Jacob; João Victor Salvador Deprá; João Pedro Pires Porto; Fernanda Rocha de Lima; Mário Roberto Tavares Cardoso de Albuquerque (Universidade de São Paulo, 2022)
ABSTRACT OBJECTIVE To characterize the profile of inpatients and trend of sepsis mortality in the Brazilian Unified Health System (SUS), throughout Brazil, and in its regions separately, from 2010 to 2019. METHODS Observational, analytical and retrospective study of secondary data obtained through consultation to the Sistema de Informação Hospitalar (Hospital Information System). All incoming septicemia notifications from January 1, 2010 to December 31, 2019 were included. The following sociodemographic variables were used: sex, age, race, region and federative unit of residence. For data analysis, we used mortality and hospitalization coefficient, relative risk and Joinpoint regression. RESULTS There were a total of 1,044,227 cases of sepsis in Brazil, yielding a mean prevalence coefficient of 51.3/100 thousand inhabitants. There were 463,000 deaths from sepsis recorded, with a mean prevalence coefficient of 22.8 deaths/100,000 inhabitants. The highest rates occurred among the elderly, of brown race, and there was no significant difference between genders. The Southeast region accounted for the highest rates of hospitalization and deaths. A general trend toward increased mortality was observed in the period studied. CONCLUSION The heterogeneity of Brazil should be considered regarding socioeconomic and demographic characteristics, and differences in health investment and underreporting between regions, in order to understand the disease's epidemiological course. Finally, these findings should be correlated with other studies, in an effort to understand the behavior of the disease, and provide inputs for public and private policies in order to reduce the expressiveness of cases and deaths from sepsis in Brazil.